No Rules Tonight - Kim, Hyun Sook; Estrada, Ryan, 1980- (New York : Penguin Workshop, 2024)
Set in dictatorial South Korea in 1984, a group of teens experience a taste of freedom on a winter retreat with no parental supervision.
new ya book 2024 fall.
Ages 12 and up.
Keywords: Freedom -- Fiction; Camps -- Fiction; Friendship -- Fiction; Korea (South) -- Fiction; Graphic novels